Whole Genome Sequencing and Re-sequencing of the Sable Antelope (Hippotragus niger): A Resource for Monitoring Diversity in ex Situ and in Situ Populations - Klaus-Peter Koepfli; Gaik Tamazian; David Wildt; Pavel Dobrynin; Changhoon Kim; Paul B. Frandsen; Raquel Godinho; Andrey A. Yurchenko; Aleksey Komissarov; Ksenia Krasheninnikova; Sergei Kliver; Sofia Kolchanova; et al. (G3: Genes, Genomes, Genetics, 2019)
Genome-wide assessment of genetic diversity has the potential to increase the ability to understand admixture, inbreeding, kinship and erosion of genetic diversity affecting both captive (ex situ) and wild (in situ) populations of threatened species. The sable antelope (Hippotragus niger), native to the savannah woodlands of sub-Saharan Africa, is a species that is being managed ex situ in both public (zoo) and private (ranch) collections in the United States. Our objective was to develop whole genome sequence resources that will serve as a foundation for characterizing the genetic status of ex situ populations of sable antelope relative to populations in the wild. Here we report the draft genome assembly of a male sable antelope, a member of the subfamily Hippotraginae (Bovidae, Cetartiodactyla, Mammalia). The 2.596 Gb draft genome consists of 136,528 contigs with an N50 of 45.5 Kbp and 16,927 scaffolds with an N50 of 4.59 Mbp. De novo annotation identified 18,828 protein-coding genes and repetitive sequences encompassing 46.97% of the genome. The discovery of single nucleotide variants (SNVs) was assisted by the re-sequencing of seven additional captive and wild individuals, representing two different subspecies, leading to the identification of 1,987,710 bi-allelic SNVs. Assembly of the mitochondrial genomes revealed that each individual was defined by a unique haplotype and these data were used to infer the mitochondrial gene tree relative to other hippotragine species. The sable antelope genome constitutes a valuable resource for assessing genome-wide diversity and evolutionary potential, thereby facilitating long-term conservation of this charismatic species.